2022
DOI: 10.1002/cam4.5118
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the skeletal muscle index on pharmacokinetics and toxicity of fluorouracil

Abstract: Background The body composition of patients has been associated with tolerability and effectiveness of anticancer therapy. This study aimed to assess the influence of the skeletal muscle index (SMI) on the pharmacokinetics and toxicity of fluorouracil. Methods Patients treated in an oncological practice with fluorouracil‐based chemotherapy and undergoing therapeutic drug monitoring were retrospectively investigated. Computed tomography images were analyzed to measure ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In the Pop-PK analyses, all PK parameters and their IIVs as defined in the original publications [28,29] could be estimated for all data splits. The mean estimated parameter values were in a similar range to the original estimated values for the whole datasets as depicted in Table 2 and the ߟ values appeared to be normally distributed for all tested methods.…”
Section: Population Pharmacokinetic Modeling Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the Pop-PK analyses, all PK parameters and their IIVs as defined in the original publications [28,29] could be estimated for all data splits. The mean estimated parameter values were in a similar range to the original estimated values for the whole datasets as depicted in Table 2 and the ߟ values appeared to be normally distributed for all tested methods.…”
Section: Population Pharmacokinetic Modeling Resultsmentioning
confidence: 99%
“…Our proposed MMPK-SciML model was able to predict the population volume for 5FU, which was impossible to obtain with FOCE-I due to convergence problems [29]. We observed that the predicted volume was often overpredicted, which could be due to outliers in the training data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations